(untitled) (Journal of Partial Differential Equations, 2020)
An existence and uniqueness result of a renormalized solution for a class of doubly nonlinear parabolic equations with singular coefficient with respect to the unknown and with diffuse measure data is established. A comparison result is also proved for such solutions.